2018
DOI: 10.1038/s41388-018-0381-2
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of tuberous sclerosis complex 2 sensitizes tumors to nelfinavir−bortezomib therapy to intensify endoplasmic reticulum stress-induced cell death

Abstract: Cancer cells lose homeostatic flexibility because of mutations and dysregulated signaling pathways involved in maintaining homeostasis. Tuberous Sclerosis Complex 1 (TSC1) and TSC2 play a fundamental role in cell homeostasis, where signal transduction through TSC1/TSC2 is often compromised in cancer, leading to aberrant activation of mechanistic target of rapamycin complex 1 (mTORC1). mTORC1 hyperactivation increases the basal level of endoplasmic reticulum (ER) stress via an accumulation of unfolded protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…However, the same treatments display no genotype specific toxicity in NCCs. These latter findings are in contrast to previous studies demonstrating the potential therapeutic effectiveness of these treatments in vitro; however, we note that the TSC2-deficient cell types used in these studies were murine cell lines with limited tissuespecific relevance to TSC tumors (Babcock et al, 2013;Johnson et al, 2018;Zhou et al, 2009). Indeed, in a preclinical trial using a Tsc2 +/mouse model, bortezomib treatment was ineffective in targeting mesenchymal renal tumors (Auricchio et al, 2012).…”
Section: Discussioncontrasting
confidence: 76%
“…However, the same treatments display no genotype specific toxicity in NCCs. These latter findings are in contrast to previous studies demonstrating the potential therapeutic effectiveness of these treatments in vitro; however, we note that the TSC2-deficient cell types used in these studies were murine cell lines with limited tissuespecific relevance to TSC tumors (Babcock et al, 2013;Johnson et al, 2018;Zhou et al, 2009). Indeed, in a preclinical trial using a Tsc2 +/mouse model, bortezomib treatment was ineffective in targeting mesenchymal renal tumors (Auricchio et al, 2012).…”
Section: Discussioncontrasting
confidence: 76%
“…( Figure 6 B, Supplementary Table S4 ). Mutation of TSC2 and its leading activation of MTORC1 upregulates the proteasome [ 30 ], which may facilitate estrogen-enhanced survival of tumor cells [ 31 , 32 ]. MTOR also activates NF-κB [ 33 ], a major regulator of cell survival, pro-inflammatory cytokines such as TNF-α, and cell adhesion molecules which may allow LAM cells to survive [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, rapamycin was very efficient at shrinking the tumor volume, but after removal of rapamycin, cells within the tumor quickly recovered. In contrast, Nelfinavir and Bortezomib were effective at killing the tumors in vitro, where there was not cell recovery after removal of this drug combination (Johnson et al, 2018). These studies demonstrate a potent cytotoxic response to TSC-diseased cells with ER stress inducers, which are tolerated by the normal cells with an intact TSC1/TSC2 signaling pathway (Fig.…”
Section: Figmentioning
confidence: 84%
“…Forward research progress has been made regarding testing ER stress inducers as a potential therapy for TSC. Recent studies showed that combinatory therapy with an ER stress inducer, Nelfinavir, in the presence of an autophagy inhibitor, Chloroquine (Johnson et al, 2015), or a proteosomal inhibitor, Bortezomib (Johnson et al, 2018), showed promise in both in vitro and in vivo models of TSC to reduce tumor size and to selectively kill the TSC-diseased cells. There was a marked difference when comparing rapamycin to these drug combinations.…”
Section: Figmentioning
confidence: 99%